Analisis Pengaruh Intensitas Cahaya Terhadap Pengisian Baterai Sprayer Hybrid Menggunakan Panel Surya Dengan Metode Fuzzy Logic - Faiz Ardiansyah; Agus Sulistiawan; Aprillia Dwi Ardianti (Universitas Muhammadiyah Yogyakarta, 2025)
The use of electric sprayers for pesticide application in Jipang Village, Blora, faces challenges due to battery dependency, often leading to inefficiencies when batteries deplete mid-operation. This study evaluates the performance of a hybrid sprayer integrated with a 10W monocrystalline solar panel and a Pulse Width Modulation (PWM) charge controller to optimize field battery charging. Experimental methods included measuring solar irradiance (using a lux meter), voltage, current, and system efficiency across three days (21 May, 29 May, and 1 June 2025) at hourly intervals (08:00–16:00 WIB). Results indicate peak efficiency (15–18%) during morning hours (08:00–10:00 WIB) under high irradiance (900–1045 W/m²), while afternoon efficiency dropped to 7–13% due to declining sunlight intensity and suboptimal solar angles. The highest power loss (60–71W) occurred at 09:00–10:00 WIB, attributed to energy conversion limitations. The study concludes that solar-hybrid sprayers are viable for agricultural use, provided battery charging is prioritized in the morning. This solution enhances operational efficiency while reducing carbon emissions and fossil fuel reliance.